Serum selenium status of HIV-infected children on care and treatment in Enugu, Nigeria. - A Ubesie; B C Ibe; I J Emodi; K K Iloh (South African Medical Association, 2017)
Objective. To compare the selenium status of HIV-infected and HIV-uninfected children. Methods. This was a hospital-based comparative study using a structured questionnaire in the quantitative research domain at the University of Nigeria Teaching Hospital, Ituku/Ozalla, Enugu, Nigeria. Seventy-four HIV-infected children were compared with 74 non-HIV-infected children (35 males and 39 females in each group). The outcome measure was the selenium status of the study participants. Results. The mean (standard deviation (SD)) weight-for-height z-score among the subjects was -0.18 (1.53) compared with 0.05 (1.68) among the controls (p=0.457). The mean (SD) height-for-age z-score among the subjects was -1.16 (1.44) compared with 0.06 (1.06) among the controls (p<0.001). Eighteen subjects (24.3%) compared with eight controls (11.4%) were selenium deficient (odds ratio 2.49; 95% confidence interval 1.00 - 6.18; p=0.044). Median CD4 counts of selenium-deficient and non-deficient subjects were 765.5 (range 409 - 1 489) and 694.0 (range 85 - 2 196) cells/μL, respectively (p=0.321). The proportions of selenium deficiency were 26.4% and 22.2% in the highly active antiretroviral therapy (HAART) and pre-HAART groups, respectively (p=0.565). Conclusion. There was a significant difference in the proportion of HIV-infected children who were selenium deficient compared with their uninfected counterparts.